2021
DOI: 10.1007/s00167-020-06398-3
|View full text |Cite
|
Sign up to set email alerts
|

Over-constrained kinematic of the medial compartment leads to lower clinical outcomes after total knee arthroplasty

Abstract: Purpose To investigate if postoperative clinical outcomes correlate with specific kinematic patterns after total knee arthroplasty (TKA) surgery. The hypothesis was that the group of patients with higher clinical outcomes would have shown postoperative medial pivot kinematics, while the group of patients with lower clinical outcomes would have not. Methods 52 patients undergoing TKA surgery were prospectively evaluated at least a year of follow-up (13.5 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The absence of pre-operative investigation was required by our IRB with the speciic aim of reducing overall X-ray exposure per patient. Moreover, although 9 months can be considered a short-term follow-up, it is in line with literature on the irst post-operative TKA kinematical analysis [9,10]. The motor task investigated was not standardized in terms of velocity and starting knee lexion angle to allow patients moving naturally and investigate daily life kinematics as much as possible.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The absence of pre-operative investigation was required by our IRB with the speciic aim of reducing overall X-ray exposure per patient. Moreover, although 9 months can be considered a short-term follow-up, it is in line with literature on the irst post-operative TKA kinematical analysis [9,10]. The motor task investigated was not standardized in terms of velocity and starting knee lexion angle to allow patients moving naturally and investigate daily life kinematics as much as possible.…”
Section: Discussionmentioning
confidence: 87%
“…2 and 3). Pizza et al recently demonstrated that a tighter medial compartment is associated with lower clinical score [10]. This might imply that, if correctly balanced, the congruence of the UC insert can control the movement of the condyles, but at the expense of non‐physiological kinematics, as also demonstrated by Daniilidis et al [6].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The 6 degrees of freedom kinematic quantitative data were calculated using the Grood and Suntay decomposition in dedicated software in MATLAB (R2016a; MathWorks Inc) using a validated workflow with submillimetric accuracy (0.22 ± 0.46 mm and 0.26° ± 0.2° for the model position and orientation, respectively). 1 , 10 The test-retest reliability was assessed using a set of repeated tests under different image noise conditions, 27 , 41 and the average error 8 was <0.48 mm (95% CI, 0.15-0.80 mm). The RSA operator was blinded to the surgical technique.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that the postoperative knee kinematics was related to the patientreported outcome measures (PROMs) [12][13][14]. Van Onsem et al reported that the high PROM group had more pronounced posterior translation laterally from 60° to 90° of exion than the low PROM group [15].…”
Section: Introductionmentioning
confidence: 99%